SURGICAL TACTICS IN COMBINED GYNECOLOGICAL AND SURGICAL PATHOLOGY - Ganiev F.I. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The problem of surgical treatment of combined diseases of the abdominal organs has long attracted the attention of specialists in various fields. The combination of diseases of the abdominal organs and female genital organs is quite common and, according to various authors, ranges from 2.8 to 63%, in particular, diseases of the appendix accompany gynecological pathology in 3.1 - 3.3%, gall bladder - in 3 ,1 - 15% [4,6,7,8]. Simultaneous surgery is the simultaneous performance of two or more independent operations for various diseases for which surgical treatment is indicated [5]. Improving the diagnostic capabilities of practical medicine, improving anesthesiology and resuscitation during surgical interventions, and introducing new minimally invasive technologies into medical practice make it possible to perform surgical interventions less traumatic, with minimal blood loss, significantly reducing the duration of the postoperative period. This creates real conditions for expanding the indications for simultaneous operations, reducing the number of intra- and postoperative complications, reducing the patient’s time in hospital and the duration of temporary disability, and represents broad prospects for improving the results of surgical treatment of patients with concomitant diseases [1,3].